(untitled) (Nigerian Journal of Technology, 2018)
This Research is based on geophysical survey of the ground water development of Okha community along Sapele Road in Benin City. The Schlumberger configuration was used for a total spread (L) of 400m. The location geographical coordinates in WGS84 is: N50 10’ 51.540’’ E60 12’ 58.080’’ and with Ellipsoidal height of 37 m. The results indicate that seven sub layers were identified as reflected from the table. The result of data processing by the software package was integrated in order to arrive at the realistic composition and layering of the subsurface. The interpretation suggested that the area was underlain with substantive aquiferous formation but at a depth not exceeding 93.4 metres (306.43 ft). However, adequate borehole logging of the samples from well bore to enable the proper screening of the aquifer zones which are captured is recommended. http://dx.doi.org/10.4314/njt.v37i3.3